Development of Magic Card Augmented Reality to Improve Critical Thinking Skills of Fifth Grade Students - Hasya, Muhammad Jundan; Widodo, Susilo Tri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
Students’ critical thinking skills in learning the history of the birth of Pancasila remain relatively low, primarily due to the limited variation of learning media and the underutilization of technology. This study seeks to develop an augmented reality magic card based on assembler edu and to examine its feasibility and effectiveness in enhancing students’ critical thinking skills. The research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed media integrates augmented reality technology with artificial intelligence support to present historical content in an interactive manner. Validation results indicated feasibility scores of 96.25% from media experts and 95% from subject matter experts, both classified as very feasible. Effectiveness testing revealed a T-test significance value of 0.000, with N-Gain scores of 0.68 in the small group and 0.65 in the large group, categorized as moderate. These findings indicate that the Assembler Edu-based augmented reality magic card media is highly feasible and effective in improving students’ critical thinking skills in learning the history of the birth of Pancasila.